Manual de evaluación de impactos ambientales en la constructora Ingtec (2023)
Ingtec is a construction company located in the municipality of Duitama. It provides services to public entities, focusing on construction projects such as bridges, roads, sports facilities, roofs, water and sewer rehabilitation, and other related projects. In the construction and development activities, environmental alterations have been observed due to changes or modifications. Therefore, it is necessary to carry out a proper analysis and evaluation of the impacts associated with their projects as part of the company's operational management. Based on this, there is a need to develop a manual that contributes to strengthening sustainable practices and ensuring compliance with environmental standards, which is the purpose of this project. To achieve this, a qualitative methodology has been selected, consisting of three phases: diagnosis, manual design, and formulation of recommendations. The document also provides an overview of the results obtained through the evolution of manual formulation. An analysis of the results is conducted, followed by a detailed evaluation of its applicability and effectiveness in assessing the impacts before, during, and after construction works, contributing to the continuous improvement of the environmental needs identified by the company.